2022
DOI: 10.1063/5.0098216
|View full text |Cite
|
Sign up to set email alerts
|

Laser fluence dependence of stoichiometry and superconductivity of iron chalcogenide superconducting films on metal tapes

Abstract: Iron chalcogenide Fe(Se,Te) films with thicknesses of 150 nm were deposited on CeO2-buffered metal tapes via pulsed laser deposition using various laser fluences. The film crystallinity and stoichiometry improved upon increasing the laser fluence. This was explained by the ablation threshold that the superconducting performance was better at higher laser fluences and was attributed to the joint contribution of higher Te contents, better texture, and strengthened in-plane strain. In addition, the pinning mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…This is caused by the lack of iron in FST films, resulting in a relatively high amount of the semiconductor elements Se and Te. 37,46 A criterion of 10% and 90% of the normal state resistance at 20 K is used to define 𝑇 zero c and 𝑇 onset c , respectively. The difference between 𝑇 zero c and 𝑇 onset c is defined as the transition width Δ𝑇 c .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is caused by the lack of iron in FST films, resulting in a relatively high amount of the semiconductor elements Se and Te. 37,46 A criterion of 10% and 90% of the normal state resistance at 20 K is used to define 𝑇 zero c and 𝑇 onset c , respectively. The difference between 𝑇 zero c and 𝑇 onset c is defined as the transition width Δ𝑇 c .…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the resistance of all FST films decreases with increasing temperature in the normal state, exhibiting a semiconducting behavior. This is caused by the lack of iron in FST films, resulting in a relatively high amount of the semiconductor elements Se and Te 37,46 . A criterion of 10% and 90% of the normal state resistance at 20 K is used to define Tnormalczero$T_{\mathrm{c}}^{{\mathrm{zero}}}$ and Tnormalconset$T_{\mathrm{c}}^{{\mathrm{onset}}}$, respectively.…”
Section: Resultsmentioning
confidence: 99%